Somatosensory evoked potentials and their relation to microstructural damage in patients with multiple sclerosis—A whole brain DTI study - Hamann, Jan; Ettrich, Barbara; Hoffman, Karl Titus; Then Bergh, Florian; Lobsien, Donald (Frontiers in Neurology, 2022)
Introduction: Somatosensory Evoked Potentials (SSEP) play a pivotal role in the diagnosis and disease monitoring of Multiple Sclerosis (MS). Altered latencies can be a marker for demyelinisation. This study aimed to evaluate correlations of SSEPs with cerebral microstructural integrity as measured by magnetic resonance imaging and diffusion tensor imaging (DTI). Analysis was performed in a hypothesis free whole brain approach using tract-based special statistics (TBSS). Material and Methods: 46 Patients with MS or clinical isolated syndromes were included into the study. Bilateral SSEPs of the median nerve measuring mean N20-latencies and Brain Conduction Time (BCT), were acquired. MRI scans were performed at 3T. DTI acquisition was done with single-shot echoplanar imaging technique with 80 diffusion directions. A freely available software package (FSL, FMRIB, Oxford, Great Britain) was used to process the DTI datasets and calculate maps of fractional anisotropy (FA), axial diffusivity (AD) and radial diffusivity (RD). These maps were than further analyzed using the TBSS module of the FSL-suite. The mean N20 and BCT were separately correlated to FA, AD and RD, controlled for age and gender as variables of non-interest. Results: Widespread negative correlations with FA and positive correlations with RD were measured in distinct white matter tracts, especially the optic tracts, corpus callosum and posterior corona radiata. No correlation with AD was found in any white matter tract. Conclusion: Highly significant correlations of FA and RD to SSEPs demonstrated widespread microstructural change in patients suffering from MS, reaching beyond the classic somatosensory regions. This underlines the systemic aspect of the disease and points to the usefulness of SSEPs as a noninvasive tool in the evaluation of microstructural damage to widespread areas of the brain.